Model And Control Of Double Link Flexible Robotic Manipulator System For Spatial Trajectory Tracking Following Task - Mohamad Iqhmannabil, Karim (2022)
In most current sectors, the use of a robotic manipulator with a double-link structure has a significant impact. The use of controllers in flexible manipulators has recently gained a lot of attention in a variety of fields of research. Many academics are working on developing controllers to prevent manipulators' errors. The modelling and control of a double-link flexible robot manipulator are presented in this study. Controlling the movement of a double-link manipulator, on the other hand, has proved to be a challenging task, especially when a flexible framework is used. Moreover, most model of double link flexible manipulator system is not developed based on real hardware. Hence, this project aim is to develop Solidworks design for double link flexible robotics manipulator (DLFRM) as well as real hardware prototype. The control position performance of DLFRM is analysed and the controllers is tested on hardware prototype. This project started with simulation of both of the controllers which is PID and FLC. The simulation was design from Solidworks and exported to Simulink and will converted as Simscape. Then, the hardware for each controller will be validated by using the control parameter in simulation. The joints for robot manipulator are design in Solidwork and built using 3D printing. As a result, in simulation, PID has better performance for both links in reducing settling time and rise time which is 0.5053s, 0.5308s for link1 and 0.2344s, 0.3799s for link 2 respectively. However, FLC outperforms PID controllers for both links in reducing overshoot and steady state error which is 14.07%, 0.005 for link1 and 11.9817%, 0.0005 for link2 respectively. As for hardware results, PID shows better performance in reducing overshoot and settling time for both links which is 2.2222%, 1.088s for link1 and 12.2211%, 2.504s for link2 respectively. On the other hand, FLC outperform PID controller for both links in reducing rise time and steady state error which is 0.44s, 0 for link1 and 0.1531s,1 for link2 respectively.